Solid-state laser with self-stabilized or linearly chirped output frequency - Lopiitchouk, M.; Peshko, I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
The specific regimes of the linear tuning and the frequency self-stabilization were proposed and analyzed theoretically in a diode pumped solid-state laser with a thin-film metallic selector.